What can we learn on Chinese aid allocation motivations from new available data? A sectorial analysis of Chinese aid to African countries - Marlène Guillon; Jacky Mathonnat (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
Since the creation of the Forum on China-Africa Cooperation (FOCAC) in 2000, Chinese official development assistance (ODA) to Africa has increased drastically. Only few analyses on the determinants of Chinese ODA allocation to African countries are available. Moreover, existing literature mainly focused on total aid flows while Chinese motivations for aid allocation might differ depending on the ODA sector considered. Our objective is to study the factors associated with Chinese aid allocation to African countries by sector between 2000 and 2014. We consider 3 ODA broad sectors as defined by the Organisation for Economic Cooperation and Development (OECD): the social infrastructure and services sector, the economic infrastructure and services sector and the production sector. Chinese ODA is measured using the AidData's Global Chinese Official Finance Dataset, 2000-2014, Version 1.0, released in fall 2017. Over the 2000-2014 period, China allocated 971, 218 and 138 ODA projects to African countries in the social infrastructure and services sector, the economic infrastructure and services sector and the production sector respectively. Between 2000 and 2014, the economic infrastructure and services sector was the first sector in terms of ODA amount with a total of US18.9 billion ahead from the social infrastructure and services sector with US7 billion or the production sector with US3.1 billion. Results of our analysis suggest that the motivations of Chinese aid allocation to African countries differ by sector. Chinese ODA in the social infrastructure and services sector appears responsive to the economic needs of recipient countries but is also driven by foreign policy considerations. Chinese economic interest, in particular for natural resources acquisition, is associated with China's ODA allocation in the economic infrastructure and services sector. Finally, while institutions in recipient countries are not related to Chinese ODA in the social infrastructure and services sector, we find that China allocates more ODA in the economic infrastructure and services sector and the production sector to African countries with weaker institutions. One of the strong conclusions of this study is to show that considering only China's overall aid to Africa can be misleading as to its underlying determinants, and therefore to point out the need to disaggregate the analysis by ODA sectors.
Keywords: F35; 330; Official development assistance; China; Africa; sectorial analysis.